Application of new eco-friendly LCMs for combating the lost circulation in heavy-weight and oil-based mud. Issue 18 (6th March 2018) - Nasiri, Alireza; Ameri Shahrabi, Mohammadjavad; Keshavarz Moraveji, Mostafa
Abstract : This study investigates the effectiveness of different lost circulation materials (LCMs) in controlling the lost circulation of heavy-weight and oil-based mud. Abstract : This study investigates the effectiveness of different lost circulation materials (LCMs) in controlling the lost circulation of heavy-weight and oil-based mud. The bridging material tester (BMT) and three-dimensional fractures were used to evaluate the fracture sealing performance of different additives. Two new eco-friendly LCMs, namely, RIPI-LQ and X1-Seal were used in the present study. RIPI-LQ was made from a special type of grass and X1-Seal additive was made from a flowering plant. Due to eco-friendly characteristics of these two additives, the risk of environmental effect was reduced. The experimental results clearly indicated that the performance of these new additives was superior to widely used LCMs such as Quick Seal, mica, oyster shell and walnut shell. Finally, the results of this study were validated using a field test. The field test results demonstrated that these new eco-friendly LCMs were able to control different types of lost circulation.